2016
DOI: 10.1007/s11892-016-0762-2
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Hypoglycemia in Children and Adolescents and Their Parents with Type 1 Diabetes

Abstract: Hypoglycemia is a frequent occurrence in children and adolescents with type 1 diabetes. A variety of efforts have been made to standardize the definition of hypoglycemia and to define one of its most significant psychosocial consequences-fear of hypoglycemia (FOH). In addition to documenting the experience of FOH in children and adolescents type l diabetes and their parents, studies have investigate the relations between FOH and glycemic control and diabetes technology use. This review provides a summary of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
110
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 58 publications
(97 reference statements)
2
110
2
4
Order By: Relevance
“…20 As a measure of validity, we correlated our modified HFS-PYC questionnaire with children self-monitoring blood glucose levels. While previous research has been inconsistent regarding the association between parents' FH and children's glycemic control, 5,8,9 our findings revealed that the HFS-PYC worry subscale was negatively associated with children's average daily blood glucose and the percent of very high glucose levels and positively associated with the percent of blood glucose levels in the target range. It is possible we were able to measure these associations, while past research was not, because we employed a very specific definition of target blood glucose according to Bergenstal et al's 21 recommendations for standardizing glucose reporting.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…20 As a measure of validity, we correlated our modified HFS-PYC questionnaire with children self-monitoring blood glucose levels. While previous research has been inconsistent regarding the association between parents' FH and children's glycemic control, 5,8,9 our findings revealed that the HFS-PYC worry subscale was negatively associated with children's average daily blood glucose and the percent of very high glucose levels and positively associated with the percent of blood glucose levels in the target range. It is possible we were able to measure these associations, while past research was not, because we employed a very specific definition of target blood glucose according to Bergenstal et al's 21 recommendations for standardizing glucose reporting.…”
Section: Discussioncontrasting
confidence: 68%
“…1,2 Hypoglycemia is potentially dangerous because it can lead to uncomfortable counter-regulatory symptoms such as headaches, dizziness, confusion, irritability, weakness, sweating, a racing pulse, and neuroglycopenia. 1,[3][4][5] Moreover, in young children (<8 years old), repeated episodes of hypoglycemia have been linked to at least transient problems with attention management, information processing, and executive functioning. 6 Due to their heightened sensitivity to insulin, erratic eating behaviors, unpredictable activity levels, and difficulty in recognizing or reporting symptoms, young children tend to be highly susceptible to episodes of hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, hypoglycemia is one of the most common acute complications in diabetes treated with insulin and the risk of hypoglycemia can become a psychological obstacle to receiving optimal glycemic control [8]. Severe hypoglycemia is still a huge problem in the group of pediatric patients: rates ranging from 5 to 12% [9]. It is not only related to unpleasant symptoms but can also frighten pediatric patient and caregivers as well.…”
Section: Discussionmentioning
confidence: 99%